PELATIHAN DAN PENDAMPINGAN DIVERSIFIKASI PRODUK PERIKANAN SERTA STRATEGI PEMASARAN SEBAGAI UPAYA PENINGKATAN PENDAPATAN MASYARAKAT DESA GUNUNGPRING, KECAMATAN MUNTILAN, KABUPATEN MAGELANG - Orbawati, Eny Boedi; Armando, Eric; Jalunggono, Gentur; Jailani, Abdul Qadir; Nofreeana, Andri; Tartila, Shobrina Silmi Qori (JURNAL KASTARA, 2022)
Low optimization of fishery product diversification development becomes the fish farmer problem in Magelang District, although capable of increasing the selling value and creating the business opportunities for fishery products. In addition to product diversification, a marketing strategy needs to be performed, so the product absorption and demand are easier in the market. Based on this condition, community service actions were carried out to train and assist the process of fishery product diversification production and marketing strategies to increase the community income. This activity was held in Wonosari Hamlet, Gunungpring Village, Muntilan District, Magelang Regency, from September - October 2022. The service participants were residents of Wonosari Hamlet, especially housewives. This activity was implemented through field observations, socialization, counseling, training, mentoring, monitoring, and evaluation. The diversified products that were used as objects in this activity contained fish samosas, kaki naga, high pressure smoked milkfish, and otak-otak bandeng. During the service implementation, participants were asked to produce fishery products, after being explained by the lecture team, before finally describing the marketing strategies to increase the community income, especially the Wonosari hamlet community. Based on the evaluation results, this service program has increased the understanding, skills, quality, and quantity of fishery products, which can have an impact on the regional food security through training and community assistance.